Cybersecurity : Public Sector Threats and Responses - Kim J. Andreasson (CRC Press, 2012)
The Internet has given rise to new opportunities for the public sector to improve efficiency and better serve constituents. But with an increasing reliance on the Internet, digital tools are also exposing the public sector to new risks. This accessible primer focuses on the convergence of globalization, connectivity, and the migration of public sector functions online. It examines emerging trends and strategies from around the world and offers practical guidance for addressing contemporary risks. It supplies an overview of relevant U.S. Federal cyber incident response policies and outlines an organizational framework for assessing risk.